Role of Agricultural Assistants in Agricultural Development in Thiruvananthapuram District - Ahsa Letha S (Department of Agricultural Extension, College of Agriculture, 1993)
A study entitled “Role of Agricultural Assistants in Agricultural Development in Thiruvananthapuram District” was undertaken with a view to study the role of Agricultural Assistants in agricultural development. Role was measured by studying the role perception and role performance of Agricultural Assistants as perceived by the selected Agricultural Assistants, Agricultural Officers and farmers. Characteristics of Agricultural Assistants in relation to their role perception and role performance and the constraints experienced by the Agricultural Assistants in the effective performance of their roles were also analysed. The sample consisted of 84 Agricultural Assistants, 45 Agricultural Officers and 90 farmers. Data were collected from the Agricultural Assistants and Agricultural Officers using questionnaires and an interview schedule was prepared for collecting information from the farmers. Suitable statistical techniques were employed in the analysis of the data. The results of the study indicated that the performance of Agricultural Assistants, though not excellent on all role items, was generally good. The perception of Agricultural Officers differed significantly from that of Agricultural Assistants and farmers about the role perception and role performance of Agricultural Assistants. But the Agricultural Assistants and farmers had almost similar opinion in both the role perception and role performance of Agricultural Assistants. The selected independent variables together contributed significantly to the variation in the role perception and role performance of the Agricultural Assistants. The results of constraint analysis revealed that ‘frequent transfers’, ‘too much office work’ and ‘lack of promotion opportunities and conveyance facilities’ were considered as the major constraints by the Agricultural Assistants in their effective performance. More sincere efforts must be taken by the State Government and higher officials of the State Department of Agriculture while chalking out new development programmes to be implemented through these grass root level workers.